Application of Raman Spectroscopy for the evaluation of metabolomic dynamic analysis in athletic horses - Acri, G.; Testagrossa, B.; Giudice, E.; Arfuso, F.; Piccione, G.; Giannetto, C. (Journal of Equine Veterinary Science, 2020)
Highlights: • Raman spectroscopy as suitable technique for biochemical analysis in veterinary medicine.